The University of Edinburgh’s systems submission to the MT task at IWSLT - Junczys-Dowmunt, Marcin; Birch, Alexandra (Proceedings of the First Conference on Machine Translation, Seattle, USA, 2016)
This paper describes the submission of the University of Edinburgh team to the IWSLT MT task for TED talks. We took part in four translation directions, en-de, de-en, en-fr, and fr-en. The models have been trained with an attentional encoder-decoder model using Nematus, training data filtering and back-translation have been applied for domain-adaptation purposes.